The prevalence rate of musculoskeletal disorders among police personnel in west coast, Sabah: a preliminary investigation / Alastair Tiong, Ismail Maakip and Peter Voo - Tiong, Alastair; Maakip, Ismail; Voo, Peter (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study examined the relationship between the risk factors (demographical factors, physical factors, work-life balance, psychosocial factors, workstyle, and mental health issues) among the prevalence of musculoskeletal disorders (MSDs) among police officers in west coast Sabah (n=165). The questionnaires used in this study consist of demographical factors and La Trobe Musculoskeletal Disorder Questionnaire. The data was collected and analysed with the use of SPSS version 22.0. The prevalence rate of MSDs among police officers was 34.81% with male officers (25.95%) having a higher prevalence rate than females (8.86%). Among the body parts, the neck and shoulder reported the highest frequency of prevalence of MSDs, while the middle to lower back reported the highest severity of pain.